2016
DOI: 10.1111/pbi.12658
|View full text |Cite
|
Sign up to set email alerts
|

Stable production of cyanophycinase in Nicotiana benthamiana and its functionality to hydrolyse cyanophycin in the murine intestine

Abstract: SummaryFood supplementation with the conditionally essential amino acid arginine (Arg) has been shown to have nutritional benefits. Degradation of cyanophycin (CGP), a peptide polymer used for nitrogen storage by cyanobacteria, requires cyanophycinase (CGPase) and results in the release of β‐aspartic acid (Asp)‐Arg dipeptides. The simultaneous production of CGP and CGPase in plants could be a convenient source of Arg dipeptides. Different variants of the cphB coding region from Thermosynechococcus elongatus B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Fusion of mZP3-1 to the GFP coding region, resulting in GFP-mZP3-1, led to a more than 25-fold higher accumulation of mZP3. GFP has already been used successfully to improve protein production and stability under various conditions [ 70 , 71 , 72 ]. This stabilization seems to depend not only on the GFP sequence, but also on the protein size since mZP3-3 showed a similar effect on the stability and accumulation of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…Fusion of mZP3-1 to the GFP coding region, resulting in GFP-mZP3-1, led to a more than 25-fold higher accumulation of mZP3. GFP has already been used successfully to improve protein production and stability under various conditions [ 70 , 71 , 72 ]. This stabilization seems to depend not only on the GFP sequence, but also on the protein size since mZP3-3 showed a similar effect on the stability and accumulation of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in case the plants are feed without prior extraction, the enzyme has to be stable and effective in the digestive tract, and the persistence of the feed should be sufficient to provide high amounts the CGP. Ponndorf et al (2016) could show that CphB Te, is stable enough to degrade CGP in the digestive tract of mice (Ponndorf et al, 2016). We could also demonstrate that there are no detectable differences in protein stability between CphB Te and CphE241 and that CphE241 showed a drastically higher enzyme activity, both as purified proteins under in vitro conditions and in crude leaf extracts (Ponndorf et al, 2017).…”
Section: Discussionmentioning
confidence: 78%
“…Complete CGP degradation was only observed for CphE241, but not for CphB Te , which was assigned to a drastically higher enzyme activity of CphE241 (Ponndorf et al, 2017). In a feeding study with mice, in which purified plantproduced CGP and CphB Te were added to the diet, it could be shown that the CGPase is capable to degrade CGP in the digestive tract and that the β-Asp-Arg DPs were transferred to the blood (Ponndorf et al, 2016). This should also be true for CphE al , since this CGPase type naturally occurs in the colon (Sallam and Steinbuchel, 2009a) and since it has been demonstrated that CphE al is active in a pH range from 5 to 9 (Sallam and Steinbuchel, 2011).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation